АБДУЛЛА ҚОДИРИЙ ҲАЖВИЙ АСАРЛАРИДА ҚЎЛЛАНИЛГАН АЙРИМ МОРФОЛОГИК БИРЛИКЛАР ВА ГРАММАТИК ШАКЛДАГИ ЎЗГАРИШЛАР - Пардаева, М.Х. (SCIENCE and SOCIETY, 2021)
The article analyzes the morphological units and its changes in grammatical form, some grammatical forms which construct indefinite forms of the verb, historical forms of case suffixes used in Abdulla Qodiri's comic works, the grammatical forms that form some action names, the historical forms of suffixes, and the use of directional conjugation with different variants.
Keywords: comics; morphemes; lexical unit; case suffixes; dialects and accent; target forms; participle and verb